Prospective surveillance of hospitalisations associated with varicella in New Zealand children. (3rd June 2015) - Wen, Sophie Chien‐Hui; Best, Emma; Walls, Tony; Dickson, Nigel; McCay, Hamish; Wilson, Elizabeth
Abstract : Aim: Varicella is a vaccine‐preventable disease not notifiable in New Zealand (NZ), and varicella vaccine is not funded in the National Immunisation Schedule (NIS). Hospitalisations can occur because of bacterial secondary infection and other complications, which can result in long‐term sequelae. Varicella may not be acknowledged in discharge coding when complications occur weeks after infection. Using the New Zealand Paediatric Surveillance Unit (NZPSU), the aim of this study was to document the hospitalisation burden of this disease. Methods: Cases (0–14years) of varicella and post‐varicella complications requiring hospitalisation, including stroke syndromes where varicella occurred in the preceding 6 months, were notified to NZPSU between 1 November 2011 and 31 October 2013. Herpes zoster cases were excluded. Questionnaires were used to capture demographics, clinical features, management and short‐term outcomes. Results: One hundred seventy‐eight notifications were received and 144 were confirmed cases. Overall incidence was 8.3/100 000 children per year. Fifty‐two per cent were women with a median age of 2.4 years. Māori and Pacific Island (PI) children accounted for 74% of hospitalisations, with incidence rate ratios compared with European children of 2.8 and 3.9, respectively ( P < 0.01). Complications included: infection (75%), respiratory (11%), neurological (11%), electrolyte disturbance (6%) and haemorrhagic varicella (4%). Nine per cent were immunocompromised. Median duration of hospital admission was 4 days with 9% requiring intensive care admission. There were no reported deaths; however, 19% had ongoing problems at discharge. Conclusion: Varicella has more associated morbidity than commonly perceived in immunocompetent children. Māori and PI children are more likely to have complications. This surveillance gives support for inclusion of universal varicella vaccine in the NZ NIS.